Pachydermoperiostosis Mimicking Acromegaly: A Case Report - Mi-Hye KWON,; Chung-Il JOUNG, (Archives of Rheumatology, 2012)
Pachydermoperiostosis is a rare osteoarthroder-mopathic disorder of which clinical and radiographic presentations may mimic those of acromegaly. In the evaluation of patients with acromegaloid appearances, pachydermoperiostosis should be considered as a differential diagnosis. In this article, we present a 26-year-old man who was admitted with the complaints of painful swelling and stiffness of hands, feet and ankles lasting for about six months.